The impact of informal sector on income distribution: Could concentration of income be explained by the size of informal sector? - Ghecham, Mahieddine Adnan (International Journal of Economics and Financial Issues, 2017)
This paper uses a cross-sectional data to explore the impact that informal sector has on income variation across different income categories. Instead of using GINI coefficient, the paper considers income shares of decile groups of population. The results reflect a dual role of informal sector in economy. On one hand, informal sector could reduce the gap between income earners at the bottom level of income categories. On the other hand, the size of informal sector could exacerbate the gap between top income earners and other categories indicating further concentration of income. Some implications are discussed. Keywords: Income distribution, informal sector, concentration of income. JEL Classifications: E26, O15